Development of Website-Based Digital Teaching Materials for the Jarimatika Qur'an Method: A Local Content Integration Approach - Rizki Muthmainnah Amir; Arismunandar Arismunandar; Nurhikmah H (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study employs a research and development approach to identify the need, design, validity, practicality, and effectiveness of website-based digital teaching materials for the Jarimatika Qur'an Method as local content. The development process follows the 4D model (Define, Design, Develop, and Disseminate). Data collection involved observations, document analysis, and questionnaires, analyzed quantitatively and qualitatively. The study participants included media and content experts, one first-grade teacher, and 21 first-grade students. The results indicate that: (1) students require website-based digital teaching materials to enhance their learning experience; (2) the developed digital teaching material was successfully implemented in the form of a website; (3) expert validation confirmed that the materials are valid and feasible for use; (4) teacher feedback classified the material as practical; and (5) effectiveness analysis based on student learning outcomes demonstrated a significant improvement (p<0.05). This study suggests that website-based digital teaching materials facilitate independent learning and enhance students' engagement in Qur'an memorization.